Isocitrate dehydrogenase 2 inhibitor enasidenib synergizes daunorubicin cytotoxicity by targeting aldo-keto reductase 1C3 and ATP-binding cassette transporters - Morell, Anselm; Budagaga, Youssif; Vagiannis, Dimitrios; Zhang, Yu; Laštovičková, Lenka; Novotná, Eva; Haddad, Andrew; Haddad, Melodie; Portillo, Ramon; Hofman, Jakub; Wsól, Vladimír (Archives of toxicology, 2022)
Targeting mutations that trigger acute myeloid leukaemia (AML) has emerged as a refined therapeutic approach in recent years. Enasidenib (Idhifa) is the first selective inhibitor of mutated forms of isocitrate dehydrogenase 2 (IDH2) approved against relapsed/refractory AML. In addition to its use as monotherapy, a combination trial of enasidenib with standard intensive induction therapy (daunorubicin + cytarabine) is being evaluated. This study aimed to decipher enasidenib off-target molecular mechanisms involved in anthracycline resistance, such as reduction by carbonyl reducing enzymes (CREs) and drug efflux by ATP-binding cassette (ABC) transporters. We analysed the effect of enasidenib on daunorubicin (Daun) reduction by several recombinant CREs and different human cell lines expressing aldo-keto reductase 1C3 (AKR1C3) exogenously (HCT116) or endogenously (A549 and KG1a). Additionally, A431 cell models overexpressing ABCB1, ABCG2, or ABCC1 were employed to evaluate enasidenib modulation of Daun efflux. Furthermore, the potential synergism of enasidenib over Daun cytotoxicity was quantified amongst all the cell models. Enasidenib selectively inhibited AKR1C3-mediated inactivation of Daun in vitro and in cell lines expressing AKR1C3, as well as its extrusion by ABCB1, ABCG2, and ABCC1 transporters, thus synergizing Daun cytotoxicity to overcome resistance. This work provides in vitro evidence on enasidenib-mediated targeting of the anthracycline resistance actors AKR1C3 and ABC transporters under clinically achievable concentrations. Our findings may encourage its combination with intensive chemotherapy and even suggest that the effectiveness of enasidenib as monotherapy against AML could lie beyond the targeting of mIDH2.
Keywords: IDH inhibitor; Isocitrate Dehydrogenase; AML; ATP-Binding Cassette Transporters; Leukemia, Myeloid, Acute; Humans; akutní myeloidní leukemie; Anthracyclines; ABC transportéry; antracykliny; Enasidenib; protinádorová antibiotika; Adenosine Triphosphate; AKR1C3; ABC transporters; cytarabin; adenosintrifosfát; Cytarabine; daunomycin; isocitrátdehydrogenasa; Daunorubicin; lidé; Antibiotics, Antineoplastic